NEW OSAZONE DIAGRAM FOR DETERMINATION OF TWO ALDOSES AND A KETOSE THAT FORM IDENTICAL OSAZONE - Pesyan, Nader Noroozi; Rahbari, Jalaladdin; Elahi-Rad, Saeed (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
A new and interesting osazone diagram was presented for determination and identification of a pair aldoses and a ketose that makes the same osazone. This chart facilitated the finding any aldose and/or ketose yielded the same osazone.